RELEVANSI KURIKULUM PERBANKAN SYARI’AH DENGAN DUNIA KERJA (Analisis Kurikulum Program Studi Perbankan Syari’ah STAIN Sultan Qaimuddin Kendari) - Akmal Akmal (Institut Agama Islam Negeri Kendari, 2014)
Analysis of curriculum study program of STAIN Kendari Islamic banking to its relevance to the world of work insustri sharia compliance with the industrial market pragmatism sharia. The composition and structure of the study program curriculum is designed on Islamic banking filosafi